From Birangona to Barangona: Plight and Tragedy of a War Heroine in Letters of Blood - Islam, Md. Hasibul (Integrated Journal for Research in Arts and Humanities, 2022)
This paper aims to examine the relationship between a Birangona, and the men of a patriarchal social system in Rizia Rahman's novel Rokter Okkhor (1978), translated into English as Letters of Blood (2016) by Arunava Sinha. It also explores the notion of honor as it is awarded to the war heroines and how the notion quickly changes into an idea of stigma as Barangona, which means prostitute. Yasmin, the protagonist of this novel, goes through traumatic experiences of being raped, ravaged, and tormented for a few months during the liberation war of Bangladesh in 1971. After the war of independence, the state honors her as a 'War Heroine' for her sufferings and sacrifices. Looking through the lenses of social stigma and capitalist patriarchy, this paper argues that Yasmin falls doubly victim to the grasp of the patriarchal system and ideology, and her state-awarded "honor" turns into a "stigma"; consequently, she goes through social humiliation, rejection, and violation. Furthermore, this paper also demonstrates that the men deny her the inalienable right to live an everyday life and she is pushed to a tragic journey from a war heroine to be a whore.